Analisa Metode Imagehash Untuk Mendeteksi Orisinalitas Citra Digital - Gideon Sinaga (STMIK Budi Darma, 2021)
The development of the internet at this time creates information in various forms such as images, videos, text data, audio and other media that can be spread quickly and a lot of digital data and information is presented and obtained easily. With so easily, more and more people will manipulate digital images by changing image files by editing them into text files, this will make it easier to receive and give or distribute personal data information and if the digital image is an image that must be protected, for example an image. the results of photographs, medical images, and so on. Problems such as ownership, violations in data manipulation will certainly violate the copyright of the data owner and also result in the authenticity of information in digital images that is not preserved, therefore it is a top priority in identifying the object of change in image files using the ImageHash method. Using the ImageHash Method is the process of examining the contents of an image and constructing a Hash value that uniquely identifies the input image based on the image content using the ImageHash Algorithm, this can find nearly identical images in constant time, or at worst, 0 (Ig n) time when making use of the right data structures.